Use of noninvasive ‘bug-eggs’ to enable comparative inferences on genetic mating system with and without parental information: A study in a cattle egret colony - Miño, Carolina Isabel (2017)
Colonial waterbirds such as herons, egrets and spoonbills exhibit ecological characteristics that could have promoted the evolution of conspecific brood parasitism and extra-pair copulation. However, an adequate characterization of the genetic mating systems of this avian group has been hindered by the lack of samples of elusive candidate parents which precluded conducting conventional parentage allocation tests. Here, we investigate the genetic mating system of the invasive cattle egret using hematophagous insects contained in fake eggs to collect blood from incubating adults in a wild breeding colony. We tested a protocol with a previously unused Neotropical Triatominae, Panstrongylus megistus, obtained blood samples from males and females in 31 nests built on trees, drew blood from 89 nestlings at those nests, and genotyped all samples at 14 microsatellite loci, including six new species-specific loci. We comparatively addressed the performance of parentage allocation versus kinship classification of nestlings to infer the genetic mating system of cattle egrets. In line with previous behavioral observations, we found evidence in support of a non-monogamous genetic mating system, including extra-pair paternity (EPP) and conspecific brood parasitism (CBP). Parentage allocation tests detected a higher percentage of nests with alternative reproductive tactics (EPP: 61.7%; CBP: 64.5%) than the kinship classification method (EPP: 50.0%; CBP: 43.3%). Overall, these results indicate that rates of alternative reproductive tactics inferred in the absence of parental genetic information could be underestimated and should be interpreted with caution. This study highlights the importance of incorporating samples from candidate parents to adequately determine the genetic mating system of a species. We expand knowledge on the reproductive tactics of colonial waterbirds, contributing novel data on the genetic mating system of the cattle egret, valuable for the design of management strategies for this invasive bird.